THE USE OF PUNAKAWAN â€œNOVEL GRAPHICâ€ FOR INCREASING EARLY CHILDHOODâ€™S KNOWLEDGE ABOUT CULTURAL HERITAGE - Hidayah, Nurul; Waluyo, Edi (BELIA: Early Childhood Education Papers, 2019)
This research is done based on concerns with children?s lack of knowledge about the culture. Indonesia is a country that is rich in cultural diversity. Cultural diversity in Indonesia today is beginning to experience shock. The shock is caused by the entry of foreign culture which then dominated local culture. The media for the introduction of local culture in early childhood is minimal and less attractive. The creation of local cultural media today is not comparable to the creation of foreign media, so early childhood is more comfortable with foreign cultures and less familiar with the local culture. This study aims to determine the differences and knowledge of early childhood about cultural heritage in terms of the use of Punakawan novel graphics. This study uses quantitative research with experimental methods. The research design used is Pre-Experimental Designs. The population in this study are all students in the TK (Kindergarten) Khalifah 25 Semarang who are 5-6 years old, while the sample is 32 children aged 5-6 years who became the experimental class which are given treatment by researchers using the media graphic novel books of the clown. The data collection technique in this study uses a knowledge scale of cultural heritage. The data analysis technique uses Independent Sample t-Test. The results obtained t count> t table (11,825> 2,039) and the sig value (2-tailed) 0.00 <0.05, then the hypothesis is accepted. The calculation of the percentage of cultural heritage knowledge in early childhood based on the application of novel graphic media has increased by 28% between pretest and posttest. The results of the study stated that there are differences and increased knowledge about cultural heritage in early childhood in terms of the use of Punakawan novel graphic.